E-Panchayat in Kashmir: The Smart way forward - Sowkat Ahmad Dar; Dr. Naseer Ahmad Lone (International Journal on Human-Computing Studies, 2022)
Jammu and Kashmir's government is promoting e-governance “Using information and communication technology (ICT) to bring simple, moral, accountable, responsive, and transparent (SMART) governance to the doorsteps of regular people at a reasonable cost." The e-panchayat programme has a lot of potential in rural India since it aims to modernise, transparent, and efficient panchayati raj organisations. Panchayat representatives can communicate with the rest of the world through this platform, allowing local communities to share their social, cultural, and economic activities, as well as their achievements and failures, with a larger audience. The e-Panchayat mission intends to improve e-Governance in Panchayati Raj Institutions (PRIs) across India by making extensive use of information and communication technology (ICT). E- Panchayat has built a user-friendly web-based tool to promote transparency in decentralised planning and reporting. The National Informatics Centre developed the e-panchayat software package as part of its e-governance efforts. When designing E-Panchayat, the information and knowledge management needs of Gram Panchayats were considered. The use of present day data and correspondence innovation fundamentally affects country advancement. In the on-going environment, an e-panchayat is consequently required. The objective of this exploration is to find out about the capacity of e-panchayats in the rural improvement process in Kashmir. In addition to that, the activities that the government does are outlined in the study. Also it shed a light on Lucanas associated with e- panchayat in Kashmir.